Histerese urbana: um modelo para a captura de dinâmicas urbanas testado nos centros históricos de Recife-PE e João Pessoa-PB no período noturno - Rocha, Ricardo Monteiro (2021)
This Thesis develops the concept of Urban Hysteresis having as its source the analogous concept of magnetic hysteresis from electromagnetism. Urban Hysteresis is related to the memory of urban vitality existing in parts of the city and its composition is structured through three variables: Urban Saturation, Urban Coercivity and Urban Remanence.As a methodological path, two strands were adopted.The first with an emphasis on conceptual theoretical construction and the second on a more quantitative perspective, based on the construction of a measuring scale of Urban Hysteresis through characteristic curves, called Urban Hysteresis curves, which represent the performance of urban hysteresis in the studied stretches, called Urban Magnetic Cutouts (RMUs). For the elaboration of such curves, a standard observation form was created based on the construction of specific parameters.The study was carried out in the historic centers of Recife-PE and João Pessoa-PB, during the night period.To analyze the RMUs, statistical clustering techniques were used. The RMUs were rated on a scale of High Urban Hysteresis, Medium Urban Hysteresis and Low Urban Hysteresis.Note that the RMUs belonging to the historic center of Recife have, on average, better Urban Hysteresis than the RMUs of João Pessoa.The reseach was conducted under unusual conditions as the collection period coincided with the COVID 19 pandemic. Some peculiar characteristics of the studied historic centers influenced the performance of urban hysteresis, such as the presence of Porto Digital in the historic center of Recife. The Thesis presents suggestions and indications for future work on the subject to be carried out in other cities and/or other areas of study.